Work and Words: Socialist Humanism of Karl Marx in Light of Foucault's Thesis about the Death of Men - Jativa, Tomasz (Hybris, 2019)
The aim of this paper is to compare philosophical methodologies of Karl Marx and Michel Foucault. The comparison is centered on the problem of humanism: whereas socialist humanism can be seen as a core belief of Marx's historical materialism, Foucault on the other hand is often described as the one of the most fierce critics of humanism. Presented analysis consists of: reconstruction of Marx's notion of work and its ontological and epistemological consequences, reconstruction of Foucault's critique of Marx's outlooks presented in The Order of Things and analysis of Foucault's thesis about the death of men. The author points out that the philosophical methodologies of Marx and Foucault are in fact similar to a large degree, as both philosophers can be described as materialists, nominalists. Furthermore, both for Marx and Foucault the human subject is to be thought as historical and socially manufactured being.